Class dismissed: international mobility, doctoral researchers, and (Roma) ethnicity as a proxy for social class?. Issue 1 (2nd January 2021) - Roberts, Paul
ABSTRACT: The interaction between doctoral education and social class is under-researched, yet is perceived to play an important part in securing social mobility. Research that does exist tends to focus on issues of access or transition, rather than considering experiences during the doctorate. This article focuses on doctoral students' experiences of short-term international placements, which have been strongly encouraged within the EU. The article draws on qualitative interviews conducted in 2018 with seven Roma and three non-Roma doctoral researchers on international placements from 2015 to 2017. I question the visibility/invisibility of social class when international placements are undertaken and explore why in the case of Roma doctoral researchers, there appears to be an elision of class and ethnicity. The article can be seen as contributing to a small but growing critical – as opposed to a descriptive – approach to academic mobilities research.